OPEN ACCESS TO JUSTICE EMPOWERING LEGAL EDUCATION THROUGH GOVERNMENT-FUNDED SCHOLARLY JOURNALS - Satheesh, Anjana; Chandarasekhar, Sandeep (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In the pursuit of global equity and justice, open access journals have emerged as pivotal platforms for disseminating legal knowledge and fostering educational growth within legal institutions. This paper explores the transformative role of open access journals in legal education, emphasizing their contribution to the democratization of knowledge and the facilitation of academic discourse. The analysis delves into the symbiotic relationship between legal academia and open access publications, highlighting how such resources enhance learning outcomes and equip future legal professionals with the necessary tools to advocate for justice. Furthermore, the paper examines the critical role of government financing in sustaining these journals, arguing that state support is essential for maintaining the integrity and availability of scholarly legal resources. By aligning with the Sustainable Development Goals (SDGs), particularly Goal 16, which focuses on promoting peaceful and inclusive societies for sustainable development, the provision of open access legal journals by governments stands as a testament to their commitment to ensuring public access to justice. Through a comprehensive review of current practices and policies, this study underscores the need for a concerted effort to integrate open access resources into legal education curricula. It advocates for policy reforms that mandate government funding for open access journals, thereby removing financial barriers and fostering an inclusive environment where legal knowledge is a public good, accessible to all.